The Impact of People on Budgets. - Schiff, Michael; Lewin, Ark Y. (The Accounting Review, 1970)
In this paper we have reexamined the relationship between the controller and the controlled within the organization. We have argued that this relationship revolves around the budget process and that the "controlled" exercise significant influence on the outcome of their budgets. This influence manifests itself in the amount of slack which managers (and all other participants) can incorporate into their budgets. The theoretical rationale for such dysfunctional behavior has been previously stated by a number of writers. However, except for the exploratory studies by Schiff and Lewin and Lowe and Shaw, there exist no observations or empirical evidence on how and why managers create slack. Decentralized control was expected to increase organization effectiveness due to the increased participation in decision making created on the local level and because the divisional controller was formally responsible to the corporate controller. Assuming, however, as we did, that financial budgets are no more than a mutually agreed upon control device, then the whole notion of control needs to be reexamined, particularly the role of the decentralized controller who appears to act as the divisional slack manager. Finally, if managerial desire for slack and the attendant dysfunctional consequences must be taken as given then the implications for top management actions must be reconsidered. We have suggested a pragmatic approach aimed at increasing the participation of top management in the budget process on a selective basis. Specifically we have discussed the problem of how top management could impose reasonable goals 23 through constructive reviewing of the budget at critical points during the budget preparation process. We have also recognized that top management is severely limited in its ability to undertake on such a task.